A Beautiful House for Birds - Lin, Grace (Watertown, MA : Charlesbridge Publishing, 2023)
"Olivia wants to paint a colorful birdhouse. She ends up with a pattern of stripes on the roof. Teaches young children about patterns"--
Ages 0-3
Keywords: Pattern perception -- Juvenile literature; Birdhouses -- Juvenile literature; Stripes -- Juvenile literature; Mathematics -- Juvenile literature; Board Books